Kemampuan Bakteri Endofit dalam Mengendalikan Penyakit Rebah Kecambah dan Layu Sclerotium (Sclerotium rolfsii) pada Kedelai: Bahasa Inggris - Marwan, Husda; Mulyati, Sri; Wilia, Weni (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2017)
Endophytic bacteria have potency as candidates of biological control agents to plant disease, because the bacteria as reported to be associated with plant resistance to pathogens. The study aimed to determine the ability of endophytic bacteria to inhibit the growth of Sclerotium rolfsii in vitro, and suppress damping off disease incedence and Sclerotium wilt disease severity on soybean. The ability of endophytic bacteria to inhibit S. rolfsii was carried out on 44 isolates that isolated from soybean, rice and banana. The ability of endophytic bacteria to control damping off disease was carried out on 13 isolates were selected in vitro (BE-CW1, BE-M1, BE-M2, BE-M3, BE-M4, BE-S1, BE-S6, BE-S13, BE-S14, BE -BRRG2, BE-KH1), and also fungicides and two controls (healthy plant and diseased plant). The ability of endophytic bacteria to control Sclerotium wilt was carried out on 6 isolates which showed pressure on damping off disease (BE-M1, BE-M2, BE-M3, BE-M4, BE-CW1, BE-KH2) and 2 controls (healthy plants and diseased plants).The results showed that the thirteen isolates of endophytic bacteria could inhibit mycelial growth and germination S. rolfsii. Soybean seed treatment revealed that dipping the seed in endophytic bacterial isolates suppressed damping off disease incedence with a range of 37.4 to 49.9% and Sclerotium wilt disease severity of 20.1 to 85 % , as well as reduced the mortality of soybean by 26.3 to 84.4 % . BE-KH2 isolate was able to suppress Sclerotium wilt in soybean by 85% and reduce the mortality by 67.5%.